STRATEGY PROJECT BASED LEARNING (PjBL) IMPROVING SKILLS OF STUDENTS IN LEARNING FOR THE 21ST CENTURY LEARNING MEDIA COURSE - RENY DWI RIASTUTI (Sriwijaya University Learning and Education International Conference, 2016)
In 21st Century Learning Skills have 3 skills: (1) life and career skills, (2) learningand innovation skills, and (3) Information media and technology skills. One strategyto achieve the learning skills in the 21st century is with the strategy of Project BasedLearning (PjBL). Project Based Learning abbreviated as PjBL is one of learningbased on problems using the project / activity as the media, to undertake exploration,appraisal, interpretation, synthesis, and information to produce various forms oflearning outcomes. This strategy is very suitable when applied to course learningmedia, because in this strategy have guidelines step consists of planning (planning),creating (creating or implementation), and processing (processing), which can leadstudents to produce a project / product. On the subject Media Education, students arerequired to deliver the products to take advantage of the surrounding environment(contextual) and ICT, which can be used as a media and applied to the learningprocess.